ChemInform Abstract: Control over Flexibility of Entangled Porous Coordination Frameworks by Molecular and Mesoscopic Chemistries. Issue 27 (8th July 2014) - Furukawa, Shuhei; Sakata, Yoko; Kitagawa, Susumu
Abstract Review: [28 refs.